Consumers' usage of food delivery app: a theory of consumption values. Issue 5 (4th July 2022) - Chakraborty, Debarun; Kayal, Ghadeer; Mehta, Prashant; Nunkoo, Robin; Rana, Nripendra P.
ABSTRACT: Food delivery applications (FDAs) represent a category of mobile applications that are used by consumers to order food online. The popularity of these FDAs has been growing exponentially recently, yet not much research has been carried out the topic. This study investigates consumers' acceptance of FDAs using the theory of consumption values as its theoretical basis. The model explores the association between consumption values (functional, social, emotional, conditional, and epistemic), visibility, and usage intention of FDAs. Data were collected from 440 Indian consumers and the model was tested using structural equation modeling. Except for emotional value, the results indicated a significant association between functional, social, conditional, and epistemic values and usage intention. Furthermore, visibility mediated the relationship between consumption values and usage intention. This study's theoretical and practical contributions are relevant to researchers and practitioners working in areas related to FDAs.